Analysis of Human Resource Competency Development for State Civil Servants at Gowa “Gau Mabaji” Center, South Sulawesi - Sucipto; Burhanuddin; Malik, Ihyani; Fatmawati (GoAcademica Research & Publishing, 2024)
Qualitative research from this type of single instrumental case study is aimed at providing an alternative analytical framework regarding the discourse on developing human resource competencies for state civil servants, which specifically focuses on employees at the Center for Rehabilitation and Social Protection-Sentra Gau Mabaji in Gowa Regency, South Sulawesi. We use Critical Realism as a philosophical basis and an interpretative method modified from contemporary social studies, combined with theoretical eclecticism to allow for a more dynamic analysis. The purposive sampling technique was used with certain practical and methodological considerations to select only subjects who were relevant to the research objectives as respondents. The interviews were then conducted in depth and semi-structured by focusing on three aspects: Knowledge, Utilizing the coding conducted earlier, Skills and Attitudes are identified as dimensions of competency, forming a conceptual framework to steer the analysis. The outcomes present a phenomenological depiction that elucidates diverse perspectives among state civil servants concerning the development of human resource competencies. This exploration encompasses the aspects of knowledge, skills, and attitude, examining their interrelation with the individuals' status, duties, and functions as employees in the rehabilitation and social protection service.